2004
DOI: 10.1093/hmg/ddh239
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage analysis of a composite index of neuroticism and mood-related scales in extreme selected sibships

Abstract: There is considerable evidence to suggest that the genetic vulnerabilities to depression and anxiety substantially overlap and quantitatively act to alter risk to both disorders. Continuous scales can be used to index this shared liability and are a complementary approach to the use of clinical phenotypes in the genetic analysis of depression and anxiety. The aim of this study (Genetic and Environmental Nature of Emotional States in Siblings) was to identify genetic variants for the liability to depression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 60 publications
3
69
0
1
Order By: Relevance
“…It is conceivable that this function is related to biological differences that are manifest in the personality attributes. In a genomewide linkage scan of neuroticism, a region on chromosome 6p was identified with a LOD score of 3.9 in male-male sibling pairs, while the same region had almost no signal in female-female pairs (Nash et al, 2004). If this finding were to lead to the cloning of a sex-specific neuroticism gene, it would be possible to construe that the biological basis for personality domains may be different in the sexes and that this difference may influence the relationship of stress to the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that this function is related to biological differences that are manifest in the personality attributes. In a genomewide linkage scan of neuroticism, a region on chromosome 6p was identified with a LOD score of 3.9 in male-male sibling pairs, while the same region had almost no signal in female-female pairs (Nash et al, 2004). If this finding were to lead to the cloning of a sex-specific neuroticism gene, it would be possible to construe that the biological basis for personality domains may be different in the sexes and that this difference may influence the relationship of stress to the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…In MERLIN-regress, repeated measures can be entered in the analysis as an average across occasions with further specification of the test-retest correlation and the number of measurements for each individual (in this case, varying from 1 to 5) to readjust the trait variance. 38 The intra-class correlation between the five measures was estimated in SPSS using a mixed model procedure, which allows using all available data, even of the subjects who did not participate every occasion.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] The correlation between anxiety, major depression and neuroticism is, in part, due to the presence of shared genetic factors, [10][11][12][13] an observation that has spurred attempts to map the genetic basis of neuroticism. [14][15][16] It is much easier to acquire the large samples necessary for genetic studies of neuroticism, which is assessed using a self-administered questionnaire, than it is to acquire large patient samples that require diagnostic interviews for accurate assessment of major depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…One study of extremely discordant and concordant siblings identified five loci that exceeded a 5% genomewide significance threshold, 14 but a second study, also using a selected sample, failed to identify any genome-wide significant signals. 15 One explanation for the difficulties encountered is that the proportion of genetic variance attributable to an individual locus is extremely small, so that the linkage studies are underpowered. A recent survey of some 50 metaanalyses and 752 individual studies concluded that the typical effect sizes of individual genetic variants for complex disease ranged from 1.2 to 1.6.…”
Section: Introductionmentioning
confidence: 99%